FRI0074 Pre-clinical tooth loss at arthritis onset is associated with higher disease activity and worse treatment response in a large early arthritis cohort study. (23rd January 2014) - Westhoff, G.; de Pablo, P.; Schneider, M.; Dietrich, T.; Zink, A.
Abstract : Background: Growing evidence suggests an association between periodontitis (PD) with rheumatoid arthritis (RA). Chronic PD is a major cause of tooth loss and the number of teeth may therefore, to some extent, reflect history of PD. Previous data suggest that patients with RA have fewer teeth, and that those who have experienced more tooth loss may be more likely to develop RA. Whether tooth loss is associated with increased disease activity or response to treatment in RA is unknown. Objectives: To evaluate the association between pre-arthritis tooth loss and disease activity as well as treatment response among patients with early arthritis in a longitudinal study. Methods: The study sample included 540 patients with early arthritis (<6 months) enrolled in an ongoing observational study (CAPEA 2010-2013), who were followed for 6 months. Data collection included tender and swollen joint counts (TJC28/SJC28), disease activity (DAS28), ESR, rheumatoid factor (RF), ACPA and the 2010 ACR-EULAR RA classification criteria. Study participants were categorized according to self-reported number of teeth (excluding wisdom teeth; 0-10, 11-20, 21-27, 28). Bi- and multivariate analyses were done to investigate the association between pre-arthritis tooth loss and treatment response at 6 months according to EULAR Response Criteria. Multivariable logistic regression models were performed with "moderate to no response" as the outcome measure, adjusted for age, sex, education level, body mass index (BMI <25, 25-30, >30), smoking at symptom onset (yes/no), RF and/or ACPA positivity, and the fulfillment of the 2010 ACR-EULAR RA criteria. Results: Patients (65% female) were 56±14years old and had mean symptom duration of 13±7 weeks. 59% were RF and/or ACPA positive, 67% fulfilled the new criteria for RA and 87% received a DMARD therapy. At 6 months, 52% of the patients achieved "good", 32% "moderate" and 16% "no" response according to the EULAR Response Criteria. The mean number of teeth reported at study entry was 19±9 (23.5% 0-10, 14.9% 11-20, 39.9% 21-27, and 21.6% 28 teeth). Tooth loss was associated with older age, higher BMI and smoking. Patients with ≤10 teeth also had significantly higher ESR, T/SJCs and a higher DAS28 at 6 months compared with those with >10 teeth. However, this was at least partially explained by older age. Multivariate analysis adjusting for age and the above mentioned parameters, confirmed smoking and severe tooth loss as predictors of insufficient EULAR response at 6 months (≤10 vs. 28 teeth: adj. OR 3.8, 95% CI 2.0-7.1; P<0.001; smoking vs. non-smoking: adj. OR 1.7, CI 1.1-2.4; P=0.009). None of the other parameters predicted response to therapy. Conclusions: Our results show that patients who have lost many teeth before arthritis onset have significantly higher disease activity and worse treatment response compared with those who have lost fewer teeth or none. While ascertainment of periodontal status is needed to confirm the role of periodontal inflammation in this association, these results suggest that pre-arthritis tooth loss is a predictor of disease activity and treatment response in patients with early arthritis. Disclosure of Interest: None Declared